Urinary Podocyte Excretion Predicts Urinary Protein Selectivity and Renal Prognosis - Makoto Abe; Akiko Kaiga; Takehiro Ohira; Toshihiko Ishimitsu; Akihiro Tojo (International Journal of Nephrology)
Background. Urinary podocyte excretion is related to a reduction in glomerular podocyte numbers, glomerulosclerosis, and urinary protein selectivity. To elucidate the role of urinary podocytes in proteinuria and renal prognosis and to identify the factors that cause podocyte detachment, we examined urinary podocytes in 120 renal biopsy patients. Methods. Podocytes were identified in urinary sediments stained with fluorescent-labeled anti-podocalyxin antibodies in ten high power fields. The amounts of protein bands, separated by SDS-polyacrylamide gel electrophoresis, were calculated using an image software program and the correlation with urinary podocytes was analyzed. Podocyte surface pores were observed using a low-vacuum scanning electron microscope. The renal prognosis, including induction of hemodialysis or 30% reduction in eGFR, was investigated. Results. Urinary podocyte excretion showed a higher positive correlation with albumin excretion compared to IgG, prealbumin, and transferrin. There were no significant correlations between urinary podocyte count and low molecular weight proteins, including β2-microglobulin and α1-microglobulin. The number of podocyte surface pores was positively correlated with proteinuria, suggesting enhanced albumin transcytosis. The hemodynamic pressure on the glomerular capillary wall, including products of pulse pressure and pulse rate (water hammer pressure), was positively correlated with urinary podocyte excretion. Urinary podocyte excretion and Tamm–Horsfall protein (THP) were independent risk factors for renal prognosis but were not related to response to treatment. Conclusion. Urinary podocyte excretion was correlated with urinary albumin excretion, indicating specific albumin transport by podocytes. Podocytes were detached from the glomerular capillaries by water hammer pressure and THP was involved in the renal prognosis.